2018
DOI: 10.7150/thno.21648
|View full text |Cite|
|
Sign up to set email alerts
|

circRNA Mediates Silica-Induced Macrophage Activation Via HECTD1/ZC3H12A-Dependent Ubiquitination

Abstract: Rationale: Phagocytosis of silicon dioxide (SiO2) into lung cells causes an inflammatory cascade that results in fibroblast proliferation and migration, followed by fibrosis. Circular RNAs (circRNAs) are a subclass of non-coding RNAs detected within mammalian cells; however, researchers have not determined whether circRNAs are involved in the pathophysiological process of silicosis. The upstream molecular mechanisms and functional effects on cell apoptosis, proliferation and migration were investigated to eluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
105
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 50 publications
4
105
0
Order By: Relevance
“…Previous data from our laboratory suggested that macrophage activation and apoptotic marker expression were increased in macrophages from the BALF of patients with silicosis (27, 32). We, therefore, extended our cell culture experiments to include examination of a human macrophage cell line and cells from patients with silicosis to validate our findings.…”
Section: Resultsmentioning
confidence: 78%
“…Previous data from our laboratory suggested that macrophage activation and apoptotic marker expression were increased in macrophages from the BALF of patients with silicosis (27, 32). We, therefore, extended our cell culture experiments to include examination of a human macrophage cell line and cells from patients with silicosis to validate our findings.…”
Section: Resultsmentioning
confidence: 78%
“…6 Recent studies have exhibited the role of circRNA HECTD1 in the development and progression of several diseases such as AIS and silicosis. 7,8 For example, a study discloses that knockdown of circRNA HECTD1 attenuates infract size and decreases neurological deficits in cerebral ischemia transient middle cerebral artery occlusion mouse (tMCAO) stroke models. 7 Besides that, a preliminary study based on primary cultures of alveolar macrophages from silicosis patients demonstrates that circRNA HECTD1 involves in SiO 2 -mediated inflammation cascade.…”
mentioning
confidence: 99%
“…7 Besides that, a preliminary study based on primary cultures of alveolar macrophages from silicosis patients demonstrates that circRNA HECTD1 involves in SiO 2 -mediated inflammation cascade. 8 Based on the role of circRNA HECTD1 in enlarging stroke infarct size, accelerating neurological deficits, and inflammation from previous studies, we hypothesized that circRNA HECTD1 may be involved in the development and progression of AIS. However, no clinical studies have been done in evaluating the role of circRNA HECTD1 in AIS until now.…”
mentioning
confidence: 99%
“…Bachmayr‐Heyda et al discovered a negative correlation of circRNA abundance and proliferation in lung fibrosis . Chao et al found that circHECTD1 promotes silica‐induced pulmonary fibrosis via HECTD1 . A recent study from our laboratory based on a circRNA microarray analysis identified 67 significantly dysregulated circRNAs in IPF patients, indicating the fundamental roles of circRNAs in pathological processes of lung fibrosis .…”
Section: Discussionmentioning
confidence: 97%
“…31 Chao et al found that circHECTD1 promotes silica-induced pulmonary fibrosis via HECTD1. 32,33 A recent study from our laboratory based on a circRNA microarray analysis identified 67 significantly dysregulated circRNAs in IPF patients, indicating the fundamental roles of circRNAs in pathological processes of lung fibrosis. 19 In this study, 145 differentially expressed circRNAs were identified under astilbin treatment using RNA sequencing.…”
Section: Discussionmentioning
confidence: 99%